STRATEGI GURU PENDIDIKAN AGAMA ISLAM (PAI) DALAM PENANGANAN KESULITAN MEMBACA DAN MENULIS AL-QUR’AN SISWA KELAS 4 SD N 2 SIKUNANG WONOSOBO - nurul_maftuchah, nurul maftuchah; Adi, Nugroho Prasetya; Hidayat, Muhtar Sofwan (AL-QALAM: JURNAL KEPENDIDIKAN, 2023)
The research was conducted on the basis that SD N 2 Sikunang Wonosobo has a uniqueness, namely the culture of reading the Koran before starting learning and reading asmaul husna after carrying out morning exercises, as an effort to increase student awareness of the importance of reading the Koran as a guide for Muslim life and also as an effort to increase the quality of reading Al-Quran students. This study aims to determine the difficulty of reading and writing the Qur'an for 4th grade students of SD N 2 Sikunang and to find out the strategies of Islamic religious education (PAI) teachers in overcoming difficulties in reading and writing the Qur'an for students of SD N 2 Sikunang, type the research used is field research with qualitative methods through a descriptive approach. The results of this mentoring activity are in accordance with the stages carried out by the researchers which have had an impact on SD N 2 Sikunang Wonosobo. They understand the importance of strategies to overcome learning difficulties based on the potential of each student.